حسین بن منصور حلاج اور ان کی صوفیانہ تعلیمات کا علمی وتحقیقی جائزہ: A Realistic Overview about Hussain bin Mansoor Hallaj and his teachings (Khairulummah, 2021)
A Sufi poet, teacher and philosopher, Hallaj was executed on the orders of an Abbasside caliph for uttering these words, taken to mean Hallaj as claiming himself to be God. After more than a decade of imprisonment, Hallaj was eventually executed publically in Baghdad in the year 922.He is seen by many as a revolutionary writer and teacher of his time, when practices of mysticism were not meant to be shared publically. Yet he remains a controversial figure, revered by Rumi, hated by many, he was labeled an intoxicated Sufi and is still read today. After his arrest in Sūs and a lengthy period of confinement (c. 911–922) in Baghdad, al-Ḥallāj was eventually crucified and brutally tortured to death. A large crowd witnessed his execution. He is remembered to have endured gruesome torture calmly and courageously and to have uttered words of forgiveness for his accusers. In a sense, the Islāmic community (ummah) had put itself on trial, for al-Ḥallāj left behind revered writings and supporters who courageously affirmed his teachings and his experience. In subsequent Islāmic history, therefore, the life and thought of al-Ḥallāj has been a subject seldom ignored.Here we get a realistic overview about him and his teachings.